The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.33369/jeet.2.1.59-67
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Direct and Indirect Speech Acts Performed by Main Character in the Movie Revenant Script

Abstract: This Research Entitled “An Analysis Of Direct And Indirect Speech Acts Performed By Main Character In The Movie Revenant Script”. This research was a descriptive analysis that discusses direct and indirect speech acts in movie script entitled ‘The Revenant.’ In analyzing the script, there was used theory by Yule (1996).The data in this research based on main characters’ utterances. The purpose of this analysis was to find out the types, and functions of speech act whether it is direct speech act or indirect sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Get on the boat, kid!" (Oktadistio et al, 2018) judging from this example, pragmatically what the speaker uses is an imperative sentence and its function is to order, judging from the sentence, he orders to go to the boat. It is clear and precise that the speaker is giving orders to the listeners.…”
Section: A Directmentioning
confidence: 97%
“…Get on the boat, kid!" (Oktadistio et al, 2018) judging from this example, pragmatically what the speaker uses is an imperative sentence and its function is to order, judging from the sentence, he orders to go to the boat. It is clear and precise that the speaker is giving orders to the listeners.…”
Section: A Directmentioning
confidence: 97%
“…In conclusion, depending on the context, individuals will utilize diverse approaches to communicate their intended topics and recipients of a conversation Several previous studies were conducted on the topic, as studies by Agus Hidayat (2016) found that types of speech acts are, illocutionary acts, illocutionary acts, and perlocutionary acts Woody's Utterances in Toy Story 3 Movie. Zahrida (2018) showed that 13 utterances of direct speech acts were the dominant used than indirect speech acts at least 9 utterances. The main character carries out these spoken statements in the movie Revenant Script.…”
Section: Introductionmentioning
confidence: 99%
“…There have been growing interests in the grand theme of speech acts in literary works such as the studies carried out by Altikriti (2011); Dewi (2013); Muntiningsih (2013); Made et al (2014); Oktadistio et al (2018). Altikriti (2011) explored and compared speech acts in three short stories.…”
Section: Introductionmentioning
confidence: 99%
“…However, they elaborated the existing inquiry by discussing the reasons underlying the use of speech acts. Ultimately, the recent study which has been undertaken by Oktadistio et al (2018) concentrated on examining direct and indirect speech acts on a movie script.…”
Section: Introductionmentioning
confidence: 99%